SPECIAL ISSUE: INTIMACY AND SEXUALITY AFTER CANCER - How sexuality changes in women after cancer diagnosis - Parlagreco Elena (Edisciences, 2021)
Sexual dysfunctions are a common and unpleasant side effect in women cancer survivors that can drastically impair quality of life. The resources dedicated to evaluate and treat these dramatic sequalae are limited and scarcely known. Although it is intuitive to relate the worsening of the sexual function to gynecological cancers, it is lesser known that any female cancer may affect sexual health, as a result of physiological and physical damage derived from cancer diagnosis, surgical treatment and medical therapies. Non conservative surgery (i.e. radical mastectomy/radical vulvectomy) and adverse events derived from therapies, may alter the body image making women feel less attractive and self-con dent. Vasomotor symptoms and induced menopause, related to some type of surgery, endocrine e chemotherapy agents, may contribute to dyspareunia, vaginal dryness, anatomical genital changes and reduce libido. The symptomatology caused by the presence of the tumor itself, as occurs in lung cancer, may lead to fatigue and loss of interest towards sexual activity. Moreover, the therapeutic pathway may impact quality of the relationship with the partner. In our paper we collected evidence about the prevalence of sexual dysfunction in women affected by main solid tumors. Studies on this topic are heterogenous, retrospective and designed by using different questionnaires to evaluate sexual impairment. The literature de nes sexual health as relevant issue affecting the patients’ quality of life, from the diagnosis, through the therapy, to the follow up of cancer. A deeper awareness and sensibility to sexual health is needed among healthcare providers.